Murder at the Mistletoe Ball - Book 6 - Griffo, J. D. (New York, NY : Kensington Publishing Corp., 2021)
"When Albertas 21-year-old grandson, Sergio, who has been missing for six months, shows up at the Mistletoe Ball next to a dead body, she and her estranged daughter Lisa Marie must put their past behind them and work together to clear his name before Christmas"-- Provided by publisher.
Keywords: Italian American families -- Fiction; Murder -- Investigation; Fiction; Holidays -- Fiction; Christmas fiction; Detective and mystery fiction